Sanitation sustainability, seasonality and stacking: improved facilities for how long, where and whom? - Jewitt, Sarah; Mahanta, Anjana; Gaur, Kamla (Wiley, 2018)
Despite high-profile efforts to ‘reinvent the toilet’ (Gates Foundation, 2014) and ‘end open defecation’ (UNICEF, 2016a), WHO/UNICEF, (2017) estimated that in 2015, 2.3 billion lacked access to improved sanitation and 892 million practised open defecation (OD). This has been associated with severe environmental and health impacts (Coffey, 2014; Rees, 2014; UNICEF, 2016a) which could worsen if climate change-induced flooding or extreme events facilitate the spread of water-borne disease (McMichael, et al. 2006; Papworth, et al. 2015). Although an estimated 2.1 billion gained access to improved sanitation between 1990 and 2015 (WHO/UNICEF, 2015a), the extent to which this translated into ‘an improvement in the adequacy of provision’ (Satterthwaite 2015,5) varies greatly over space, by season and between user groups. In 2015, 56% of India’s population lacked basic sanitation and 40% practised open defecation although rural-urban and socio-economic variations were significant (WHO/UNICEF, 2017). These figures almost certainly over-estimate sanitation coverage as most household-level census, Demographic and Health Survey (DHS) and Multiple Indicator Cluster Survey (MICS) data used to inform sanitation tracking do ‘not include informal urban settlements or slums, which are often not considered in official data collection’ (WSSCC, 2015:3). Dry season bias in household survey data collection (Pullum, 2008; Wright et al., 2012) coupled with seasonal shifts in sanitation practices (Routray et al 2015; Sahoo et al 2015) are likely to create further distortion. Focus on the presence of particular sanitation technologies (as proxies for sanitation access), meanwhile, can conceal significant health threats in the absence of checks on whether their quality or use is sufficient to reduce health risks (Gine et al., 2011).